Practical theology of church and world: ecclesiology and social vision in 20th century Scotland - Gay, Douglas C (My University, 2006)
The strong emphasis on ecclesiology in the work of Stanley Hauerwas, John Milbank and others associated with ‘the new ecclesiology’1 brings theological challenges to the contemporary move to recast practical theology’s attention to church and society as ‘public theology’. A historical reading of three key examples of practice in the tradition of twentieth century Scottish reformed-ecumenical reflection on ‘church and society’ displays a rich seam of reflection on ecclesiology, with some significant affinities to ‘the new ecclesiology’. The work of Stanley Hauerwas is used to develop a critical reading of the practices of theology and the theologies of (church and world) practice embedded in each example. This leads to the claim that ‘the new ecclesiology’ offers practical theology a way of articulating the church-world relationship and expressing the social, political and cultural witness of Christianity within Scotland which is to be preferred to the rubric of ‘public theology’. Its appeal for practical theology in the face of church decline and the marginalisation of theological discourse within liberal culture lies not in a temptation towards the comforts of “sectarianism”, but in its confession of the “ironic” character of the politics of Jesus and the reign of God. Its promise for practical theology lies in its claim to offer a narrative display of how theology as “church pragmatics” can mediate a fruitful social, political and cultural imagining of the world Scotland is and the world it is called to be.
A practical theology of church and world: ecclesiology and social vision in 20th century Scotland
Keywords: ecclesiology; divinity